Highly‐Packed Proximity‐Coupled DC‐Josephson Junction Arrays by a Direct‐Write Approach. (1st July 2022) - Porrati, Fabrizio; Jungwirth, Felix; Barth, Sven; Gazzadi, Gian Carlo; Frabboni, Stefano; Dobrovolskiy, Oleksandr V.; Huth, Michael
Abstract: Focused ion beam induced deposition (FIBID) is a direct‐write technique enabling the growth of individual nanostructures of any shape and dimension with high lateral resolution. Moreover, the fast and reliable writing of periodically arranged nanostructures can be used to fabricate devices for the investigation of collective phenomena and to design novel functional metamaterials. Here, FIBID is employed to prepare dc‐Josephson junction arrays (dc‐JJA) consisting of superconducting NbC dots coupled through the proximity effect via a granular metal layer. The fabrication is straightforward and allows the preparation of dc‐JJA within a few seconds. Microstructure and composition of the arrays are investigated by transmission electron microscopy and energy dispersive X‐ray spectroscopy. The superconductor‐to‐metal transition of the prepared dc‐JJA is studied in a direct way, by tuning the Josephson junction resistance in 70 nm‐spaced superconducting NbC dots. The observed magnetoresistance oscillations with a period determined by the flux quantum give evidence for the coherent charge transport by paired electrons. Moreover, the measured resistance minima correspond to two fundamental matching configurations of fluxons in the dc‐JJA, caused by magnetic frustration. The robust properties of the prepared dc‐JJA demonstrate the opportunities for a fast preparation of complex device configurations using direct‐write approaches. Abstract : Focused ion beam‐induced deposition enables nanoprinting of highly‐packed dc‐Josephson‐junction arrays (dc‐JJA) within a few seconds. The device consists of superconducting NbC‐nanodots coupled via a granular metal. The tunable coupling strength allows to study phenomena like phase transitions and magnetic frustration. The robust properties of the dc‐JJA demonstrate the opportunities for a fast preparation of complex device configurations using direct‐write approaches.